ʻIlāj kibār al-sinn bi-al-fann : taʻzīz al-tawaṣul maʻahum wa-al-irtiqāʼ bi-qadrātihim - Partridge, Erin; Partridge, Erin (Majmūʻat al-Nīl al-ʻArabīyah, 2020)
Focusing on empowerment and interpersonal connection, this book presents approaches to art therapy that increase older adults' sense of self-efficacy and encourage community engagement. With wide applications, it includes case studies from community, assisted living, skilled nursing, and dementia-care environments.